Prove: \(\lvert a \rvert \ge 0\)

Prove: \(\lvert a \rvert = 0 \longleftrightarrow a = 0\)

Prove: \(\lvert a \rvert \ge a\)

Prove: \(\lvert a \rvert^2 = a^2\)

Prove: \(\lvert ab \rvert = \lvert a \rvert \lvert b \rvert\)

1

2

Prove: \(\lvert -a \rvert = \lvert a \rvert\)

2

Prove: \(b \ne 0 \longrightarrow \left\lvert \dfrac{a}{b} \right\rvert = \dfrac{\lvert a \rvert}{\lvert b \rvert}\)

Prove: \(\lvert a - b \rvert = \lvert b - a \rvert\)

\(\lvert a - b \rvert = \lvert -(b - a) \rvert \\ = \lvert b - a \rvert\)

Prove: \(\lvert a - b \rvert \ge \lvert a \rvert - \lvert b \rvert\)

Prove: \(\lvert a - b \rvert \ge \lvert \lvert a \rvert - \lvert b \rvert \rvert\)

Prove: \(\lvert \lvert a \rvert \rvert = \lvert a \rvert\)

Prove: \(\lvert x \rvert \lt \lvert x - 1 \rvert + \lvert x + 1 \rvert\)

Prove: \(-\lvert x \rvert \le x \le \lvert x \rvert\)

Prove: \(\lvert a \rvert \le b \longleftrightarrow -b \le a \le b\)